Answer:
Point-slope form of equation given as
.
Slope-intercept form of equation is given as
.
Step-by-step explanation:
In the question, it is given that the slope of a line is -2 and it passes from (-2,2).
It is asked to write the point-slope form of the equation and rewrite it as slope-intercept form.
To do so, first find the values which are given in the question and put it in the formula of point-slope form. Simplify the equation to rewrite as slope-intercept form.
Step 1 of 2
Passing point of the line is (-2,2).
Hence,
and
![$$y_{1}=2 \text {. }$$](https://tex.z-dn.net/?f=%24%24y_%7B1%7D%3D2%20%5Ctext%20%7B.%20%7D%24%24)
Also, the slope of the line is -2.
Hence, m=-2
Substitute the above values in point-slope form of equation given by ![$y-y_{1}=m\left(x-x_{1}\right)$](https://tex.z-dn.net/?f=%24y-y_%7B1%7D%3Dm%5Cleft%28x-x_%7B1%7D%5Cright%29%24)
![$$\begin{aligned}&y-y_{1}=m\left(x-x_{1}\right) \\&y-2=-2(x-(-2) \\&y-2=-2(x+2)\end{aligned}$$](https://tex.z-dn.net/?f=%24%24%5Cbegin%7Baligned%7D%26y-y_%7B1%7D%3Dm%5Cleft%28x-x_%7B1%7D%5Cright%29%20%5C%5C%26y-2%3D-2%28x-%28-2%29%20%5C%5C%26y-2%3D-2%28x%2B2%29%5Cend%7Baligned%7D%24%24)
Hence, point-slope form of equation given as y-2=-2(x+2).
Step 2 of 2
Solve y-2=-2(x+2) to write it as slope-intercept form given by y=mx+c.
![$$\begin{aligned}&y-2=-2(x+2) \\&y-2=-2 x-4 \\&y=-2 x-4+2 \\&y=-2 x-2\end{aligned}$$](https://tex.z-dn.net/?f=%24%24%5Cbegin%7Baligned%7D%26y-2%3D-2%28x%2B2%29%20%5C%5C%26y-2%3D-2%20x-4%20%5C%5C%26y%3D-2%20x-4%2B2%20%5C%5C%26y%3D-2%20x-2%5Cend%7Baligned%7D%24%24)
Hence, slope-intercept form of equation is given as y=-2x-2.